Probabilitas Teroris Perempuan di Indonesia - Saputro, M. Endy (Jurnal Ilmu Sosial dan Ilmu Politik, 2010)
Indonesian police through Densus 88 have analyzed and predicted the strategy of terrorism in Indonesia, which was important to note that those Indonesian terrorist are males. In short, the Indonesian terrorists need to set up their strategy of attack. Will the Indonesian terrorists build a new strategy with taking involve woman within the strategy? This paper aims to understand the involvement of women terrorist in some suicide actions in global context. To sum up, this paper argues that the emergence of women terrorist in Indonesia are possible, yet it requires the precedence conditions of world women terrorists in global contexts.